Commonality in news around the world - Dang, Tung Lam; Moshirian, Fariborz; Zhang, Bohui (Journal of Financial Economics, 2015)
Motivated by the pioneering study of Morck, Yeung, and Yu (2000), this paper investigates whether and how news commonality varies according to a country׳s institutional environments. Using a unique global news data set across 41 countries for the 2000–2009 period, we document three notable findings. First, firm-level news comoves more in countries with weaker institutional environments than in those with stronger institutional environments. Second, news commonality is positively associated with both stock return comovement and stock liquidity commonality. Third, the effect of news commonality on stock return and liquidity comovement is higher in countries with stronger institutions than in those with weaker institutions. These results suggest that a country׳s institutional environments affect firm-specific information production and, more importantly, support the information-efficiency view that lower price synchronicity is caused by greater capitalization of firm-specific information.